PEMILIHAN DAN BENTUK FUNGSI MODEL EMPIRIK: STUDI KASUS PERMINTAAN UANG KARTAL RIIL - Insukindro Insukindro; Aliman Aliman (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
This paper attempts to introduce and apply some methods of model selectionin order to avoid a specification error. In general, the specification error can beindicated by three possibilities which are possible problems with: (1) disturbances,(2) explanatory variable and (3) parameters. In this paper, our discussion isconcentrated on the functional form of our estimable model. The estimated model inthis paper is the demand for real currency in Indonesia for the period of 1984(1) 1997 (IV).The empirical result show that MacKinnon, White and Davidson (MWD Test),Bera and Me A leer (B-M Test) and Zarembka tests are fail to identify the bestfunction at form of our empirical model. However, using error correction approach,the findings show the best functional form of the demand for real currency inIndonesia is the log linear regression model